One cool friend - Buzzeo, Toni.; Small, David, 1945- (New York : Dial Books for Young Readers, 2012)
Elliot, a very proper young man, feels a kinship with the penguins at the aquarium and wants to take one home with him.
Keywords: Penguins -- Fiction; Etiquette -- Fiction; Humorous stories; Etiquette -- Juvenile fiction; Humorous stories; Penguins -- Juvenile fiction; Penguins -- Fiction; Etiquette -- Fiction